A Learning Factory Implementation with Industry, Teaching and Research Perspectives - Quinn, William; Ahearn, Aaron; Buckley, Killian; Casotti, Alberto; Ozturk, Cemalettin (Procedia computer science, 2025)
In the last decade, Industry 4.0 has resulted in widespread change in how manufacturing operates and, as a consequence, the skills set that a graduating engineer is required to display. This rapid change has resulted in challenges for educational institutions at third level as mechanical and manufacturing engineering has now become a interdisciplinary profession requiring not only traditional skills but also skills in information technology, computer science, among others. The challenge in an educational setting is to develop a space where various disciplines can work together, both educators and students in an industrially relevant space. For this reason, a learning factory has been developed in the Munster Technological University with that purpose in mind. Following up on previous work, this paper presents achievements in educational, industrial interaction and research projects. The learning factory has permitted the development of masters level modules, provide training for local industry and also research in the area of machine learning, digital twin, and autonomous flexible manufacturing systems, projects which are summarised in this paper. The paper ends with a discussion of the future direction of the learning factory with the objective of sustainable growth.